Characterization of serum hormone profiles in growing heifers implanted with anabolic growth promotants - Henricks, D.M.; Kuhl, Gerry L.; Spire, M.F.; Blasi, Dale A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 147-day study was conducted to determine the sequential growth responses and serum hormone profiles of growing heifer calves implanted with anabolic growth promotants. Forty eight previously nonimplanted crossbred beef heifers averaging 396 lb were assigned to one of three treatments: 1) nonimplanted controls (NC), 2) Revalor®-G (REV-G), and 3) Synovex ®-H (SYN-H). Accumulative gain response from day 84 through the end of the trial was significantly faster for both implant treatments than controls. Implant response was not consistent across time; heifers in both implant treatments gained faster than controls (P<.05) during the early (days 22-42) and later (days 64-84 and 85-105) weigh periods. By day 2, serum estradiol concentrations were increased in REV-G (P<.05) and SYN-H (P<.01) heifers relative to NC. Only REV-G contains trenbolone acetate, and none was detected in NC and SYN-H heifers, but serum levels in REV-G heifers were increased on days 2 (P<.001), 4 (P<.05), and 63 (P<.001). Only SYN-H contained testosterone; its level peaked by day 63 in SYN-H heifers. Throughout the study, progesterone was higher in NC heifers than in SYN-H or REV-G heifers, which suggests that the exogenous steroids reduced pituitary gonadotropin secretion and, thus, ovarian progesterone secretion. Our results suggest that the release of trenbolone and estradiol from REV-G implants is complete by 84 days after implanting.
Keywords: Beef; Growth promotants; Serum hormones; Heifers